Antecedents and Consequences of Conformity in Halal Products - Damayanti, Sisca; Pratomo, Luki Adiati; Shalsabilla, De'sya; Handayani, Khoriro (Business and Entrepreneurial Review, 2024)
This research contains a discussion of the factors that influence the intention to purchase halal products. It is hoped that the results of this research will help entrepreneurs who produce halal products that suit current needs so that they are easier to adopt. The research design that will be used is hypothesis testing, data collection using non-probability methods with purposive sampling techniques, so that the criteria for respondents is the generation that uses halal products. The data will be analyzed using a Structural Equation Model which will previously carry out Validity and Reliability prerequisite tests on the data obtained. Research results: Promotion has a positive effect on conformity and conformity has a positive effect on intention to purchase halal products. And it is proven that Promotion has a positive effect on Intention to Purchase Halal Products which is mediated by Conformity. Meanwhile, the influence of Religiosity on Conformity was found to be insignificant. And conformity also does not mediate religiosity on intention to purchase halal products.